2009
DOI: 10.1080/09658210802557711
|View full text |Cite
|
Sign up to set email alerts
|

Serial position effects in 2-alternative forced choice recognition: Functional equivalence across visual and auditory modalities

Abstract: Two experiments examined Ward, Avons and Melling's (2005) proposition that the serial position function is task, rather than modality, dependent. Specifically, they proposed that for backward testing the 2-alternative forced choice (2AFC) recognition paradigm is characterised by single-item recency irrespective of the modality of the stimulus presentation. In Experiment 1 the same nonwords sequences, presented both visually or auditorially, produced qualitatively equivalent serial position functions with 2AFC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…Like change detection experiments, studies examining visual WM for serially presented items have tested recall in a binary fashion, assuming that each object in a sequence is either perfectly stored or entirely forgotten (Phillips and Christie, 1977; Smyth et al, 2005; Johnson and Miles, 2009). But this approach does not provide any information on the fidelity of stored representations.…”
Section: Introductionmentioning
confidence: 99%
“…Like change detection experiments, studies examining visual WM for serially presented items have tested recall in a binary fashion, assuming that each object in a sequence is either perfectly stored or entirely forgotten (Phillips and Christie, 1977; Smyth et al, 2005; Johnson and Miles, 2009). But this approach does not provide any information on the fidelity of stored representations.…”
Section: Introductionmentioning
confidence: 99%
“…Broadly speaking, there have already been several studies of serial visual memory (Hay, Smyth, Hitch, & Horton, 2007; Johnson & Miles, 2009; Phillips & Christie, 1977; Smyth, Hay, Hitch, & Horton, 2005; Smyth & Scholey, 1996). These studies have revealed hints of primacy and recency effects when entire spatial sequences are reproduced from visual memory (Hay et al, 2007; Smyth et al, 2005; Smyth & Scholey, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Broadly speaking, there have already been several studies of serial visual memory (Hay, Smyth, Hitch, & Horton, 2007;Johnson & Miles, 2009;Phillips & Christie, 1977;Smyth, Hay, Hitch, & Horton, 2005;Smyth & Scholey, 1996). These studies have revealed hints of primacy and recency effects when entire spatial sequences are reproduced from visual memory (Hay et al, 2007;Smyth et al, 2005;Smyth & Scholey, 1996).…”
Section: Introductionmentioning
confidence: 99%